Left 2013. Roma, 10 dicembre 2016 - Fagioli, Massimo (Il sogno della farfalla, 2017)
This article introduce to a special issue of “Il sogno della farfalla” entirely dedicated to the Italian psychiatrist Massimo Fagioli, who passed away on February 13th, 2017. Fagioli was the founder of the Human Birth Theory and of our journal. In this issue we transcribed and collected most of his recent public speeches, both at book presentations and in television broadcasts. The texts included cover a period starting in 2010 but belong mainly to the last one and half year, after the conferences of October and November 2015 celebrating the 40th anniversary of the Analisi collettiva. They allow to follow the thread of Fagioli’s research, showing how much it was active, vital and still continuously in development, in search for the most appropriate terms to describe the child’s reality, the dynamics of human birth and the definition of one’s own identity.